STIMULASI GURU PADA MOTORIK KASAR ANAK TAMAN KANAK-KANAK DI KECAMATAN KURANJI KOTA PADANG - Rina Juniarti; Izzati Izzati; Yaswinda Yaswinda (Fakultas Ilmu Pendidikan Universitas Muhammadiyah Jakarta, 2019)
This study aims to determine the stimulation carried out by teachers in the development of gross motoric children of kindergartens in kecamatan of Kuranji kota Padang. This type of research is quantitative descriptive research. The population in this study were 129 kindergarten teachers in the kecamatan of Kuranji Kota Padang, then the sampel was 27 teacher with a sampling technique that was purposive sampling. The research instrument is a questionnaire with Likert scale model that has been tested for validation and reliability. Data analysis using the formula percentage level of achievement is the average score divided by the ideal score multiplied hundred. The results of this study indicate that the teacher stimulation on the gross motor skill of the Kindergarten children in the sub district of Kuranji Padang City is in good category with an achievement level of 80,20%